Precious metal loaded amorphous metal oxide catalytic material as well as preparation method and application thereof

Through precious metal-loaded amorphous metal oxide catalytic materials, the problem of low ammonia decomposition conversion is solved, efficient ammonia decomposition hydrogen production reaction is achieved, and solar energy utilization efficiency is improved.

CN119500178AActive Publication Date: 2025-02-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311039336.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-25
Estimated Expiration
2043-08-17

AI Technical Summary

Technical Problem

The conversion rate of ammonia decomposition in the prior art is low, which limits the practical application of ammonia decomposition to hydrogen production.

Method used

A precious metal-supported amorphous metal oxide catalytic material was developed to improve reaction efficiency by combining ruthenium with amorphous nickel oxide, cobalt oxide and iron oxide.

Benefits of technology

It improves ammonia decomposition activity, enhances the utilization efficiency of near-infrared sunlight, simplifies the preparation process, and is easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500178A_ABST
    Figure CN119500178A_ABST
Patent Text Reader

Abstract

The invention relates to the field of photocatalytic conversion, and discloses a noble metal loaded amorphous metal oxide catalytic material as well as a preparation method and application thereof. The catalytic material comprises a group VIII amorphous metal oxide and ruthenium; the group VIII amorphous metal oxide is selected from at least one of amorphous nickel oxide, amorphous cobalt oxide and amorphous iron oxide; on the basis of the total amount of the catalytic material, the content of ruthenium is 0.1-6.5% by mass in terms of elements. The catalytic material provided by the invention simultaneously contains the noble metal and the amorphous metal oxide, and is rich in coordination unsaturated structures, so that surface reaction active sites can be provided, and the reaction efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalytic conversion, and in particular to a noble metal-loaded amorphous metal oxide catalytic material and a preparation method and application thereof. Background Art

[0002] Research on long-distance hydrogen transportation is being conducted both at home and abroad. At present, there are three main methods of long-distance hydrogen transportation that are most widely studied internationally: pipeline hydrogen transportation, liquid hydrogen storage and transportation, and chemical storage and transportation. The medium for chemical hydrogen storage and transportation mainly includes organic liquids, ammonia, methanol, etc. According to the International Energy Agency report, the comprehensive cost of using ammonia as a hydrogen storage medium is significantly lower than that of liquid hydrogen and organic liquid hydrogen carriers.

[0003] In the ammonia storage and transportation industry chain, ammonia synthesis and transportation technology is relatively mature, so the development of efficient ammonia decomposition technology is the key to realizing the "hydrogen-ammonia-hydrogen" hydrogen storage and transportation. Thermodynamic calculation results show that the equilibrium conversion rate of ammonia decomposition can reach 99% at normal pressure and 400°C, but the activation energy of ammonia decomposition is high and the kinetics are slow, which limits its practical application. The development of efficient ammonia decomposition catalysts is the core of realizing the industrialization of ammonia decomposition hydrogen production. At present, the commonly used catalytic conversion pathways mainly include thermal catalysis, photocatalysis and electrocatalysis. Traditional thermal catalytic methods have high energy consumption and are not conducive to large-scale application. Using solar energy to assist the catalytic process to achieve hydrogen production is expected to reduce dependence on fossil fuels. However, conventional semiconductor materials can only use ultraviolet light and a small amount of visible light, and the utilization efficiency of solar energy is limited. Amorphous semiconductor materials can effectively capture near-infrared sunlight due to their unique band tail state absorption, and their rich coordination unsaturated structure can provide surface reaction active sites, further improving the reaction efficiency. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of low ammonia decomposition conversion rate in the prior art and to provide a noble metal-loaded amorphous metal oxide catalytic material and its preparation method and application. The catalytic material contains both noble metals and amorphous metal oxides, and its rich coordinated unsaturated structure can provide surface reaction active sites to improve reaction efficiency.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a precious metal loaded amorphous metal oxide catalytic material, wherein the catalytic material comprises a Group VIII amorphous metal oxide and ruthenium; the Group VIII amorphous metal oxide is selected from at least one of amorphous nickel oxide, amorphous cobalt oxide and amorphous iron oxide; based on the total amount of the catalytic material, the content of ruthenium is 0.1-6.5% by mass in terms of element.

[0006] Preferably, the mass ratio of the amorphous cobalt oxide to the sum of the amorphous nickel oxide and the amorphous iron oxide is 1-5:1, and more preferably 1.2-3:1.

[0007] Preferably, the catalytic material contains oxygen defects.

[0008] Preferably, the content of oxygen defects in the catalytic material is 2-10%, more preferably 4-6%.

[0009] A second aspect of the present invention provides a method for preparing a noble metal-supported amorphous metal oxide catalytic material, wherein the method comprises the following steps: S1, contacting and reacting an alcohol solution A containing a Group VIII metal precursor with a carbonate solution B to obtain a reaction product; S2, in the presence of a reducing agent, subjecting the alcohol solution C containing the reaction product of step S1 to a reduction reaction with a ruthenium precursor, and then drying to obtain a noble metal catalytic material; The Group VIII metal is selected from at least one of iron, cobalt and nickel; The amount of the ruthenium precursor is such that the content of ruthenium in the prepared noble metal catalyst material is 0.1-6.5% by mass, calculated as the element, based on the total amount of the catalyst material; The conditions of the contact reaction in step S1 and the reduction reaction in step S2 independently include: temperature of 5-40° C. and time of 0.5-24 h.

[0010] The third aspect of the present invention provides a noble metal-loaded amorphous metal oxide catalytic material prepared by the preparation method described in the second aspect.

[0011] The fourth aspect of the present invention provides an application of the noble metal-loaded amorphous metal oxide catalytic material described in the first aspect or the third aspect in a photocatalytic ammonia decomposition hydrogen production reaction.

[0012] The catalytic material provided by the present invention has a rich coordination unsaturated structure by introducing amorphous metal oxides, which is beneficial to provide more noble metal growth sites and promote their dispersion, and is also beneficial to promote the adsorption and activation of reactant molecules, thereby improving ammonia decomposition activity.

[0013] The method provided by the present invention adopts a room-temperature liquid phase synthesis method to prepare an amorphous photocatalytic material, and its unique band-tail state absorption can effectively capture near-infrared sunlight. At the same time, its rich coordination unsaturated structure can provide surface reaction active sites, further improving the reaction efficiency.

[0014] The method provided by the invention has simple preparation process, good repeatability and is easy to carry out large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is an X-ray diffraction pattern of the catalytic material of Example 1 of the present invention; Figure 2 This is the absorbance curve of the catalytic material of Example 1 of the present invention. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] The first aspect of the present invention provides a precious metal-loaded amorphous metal oxide catalytic material, wherein the catalytic material comprises a Group VIII amorphous metal oxide and ruthenium; the Group VIII amorphous metal oxide is selected from at least one of amorphous nickel oxide, amorphous cobalt oxide and amorphous iron oxide; based on the total amount of the catalytic material, the content of ruthenium is 0.1-6.5% by mass in terms of element.

[0018] In the present invention, preferably, based on the total amount of the catalytic material, the content of ruthenium is 2-5% by mass in terms of element.

[0019] In the present invention, preferably, the amorphous metal oxide of group VIII is amorphous nickel oxide, amorphous cobalt oxide and amorphous iron oxide. The advantages of adopting this preferred embodiment are to provide more surface active centers by utilizing the rich interfaces of different metal oxides, and at the same time optimize the activation ability of the metal center to ammonia molecules, thereby improving the reaction activity.

[0020] In the present invention, preferably, the mass ratio of the amorphous cobalt oxide to the sum of the amorphous nickel oxide and the amorphous iron oxide is 1-5:1, and more preferably 1.2-3:1. Specifically, the mass ratio of the amorphous cobalt oxide to the sum of the amorphous nickel oxide and the amorphous iron oxide refers to the ratio of the content of amorphous cobalt oxide: (the content of amorphous nickel oxide + the content of amorphous iron oxide). In the present invention, through the coordination between amorphous cobalt oxide, amorphous nickel oxide and amorphous iron oxide, there are advantages of strong synergy between metal oxides, most suitable matching degree and highest defect concentration. When the content of amorphous cobalt oxide and the sum of amorphous nickel oxide and amorphous iron oxide is higher than the above range, there is an element segregation defect. When the content of amorphous cobalt oxide and the sum of amorphous nickel oxide and amorphous iron oxide is lower than the above range, it is not conducive to defect formation.

[0021] In the present invention, preferably, based on the total amount of the amorphous metal oxide of Group VIII, the content of the amorphous cobalt oxide is 50-80% by mass, the content of the amorphous nickel oxide is 7.5-25% by mass, and the content of the amorphous iron oxide is 7.5-25% by mass.

[0022] In the present invention, the content of each component in the catalytic material is measured by calculating the feed amount, Co is measured as CoO, Fe is measured as Fe 2 O 3 Ni is calculated as NiO and Ru is calculated as element.

[0023] In the present invention, the catalytic material provided has excellent specific surface area and can provide photocatalytic performance. Preferably, the specific surface area of ​​the catalytic material is 200-800cm 2 / g, preferably 600-800cm 2 / g.

[0024] In the present invention, the specific surface area of ​​the catalytic material is measured by BET nitrogen isothermal adsorption-desorption curve.

[0025] In the present invention, it should be noted that the amorphous metal oxide refers to a state in which the arrangement of atoms of a solid substance has short-range order and long-range disorder.

[0026] In the present invention, preferably, the catalytic material has no characteristic diffraction peak at 10°-90° in the X-ray diffraction pattern, and the catalytic material has an amorphous package characteristic diffraction peak at 30°-40° in the X-ray diffraction pattern. In the present invention, the amorphous package characteristic diffraction peak has the conventional definition of amorphous structural materials in the art, such as Figure 1 As shown, the catalytic material provided by the present invention exhibits a "mantou peak" amorphous package diffraction peak in the range of 30º-40º, and the "mantou peak" has the meaning conventionally defined in the art. The appearance of the amorphous package characteristic diffraction peak indicates that the catalytic material contains an amorphous structure.

[0027] In the present invention, preferably, the amorphous metal oxide contains oxygen defects. Oxygen defects can act as electron donors to increase the local electron concentration around the active site, and can also act as active sites to promote the reaction of the reactant NH 3 Adsorption and activation of molecules.

[0028] In the present invention, the oxygen defect in the catalytic material refers to the oxygen content in the catalytic material being less than its theoretical stoichiometric content. The oxygen defect is measured by X-ray photoelectron spectroscopy analysis. The specific test conditions are: using high-resolution O1s spectrum peak fitting to determine lattice oxygen and defect oxygen signals, and thus calculating the molar percentage of oxygen defects as: defect oxygen / (defective oxygen+lattice oxygen)×100%.

[0029] In the present invention, preferably, the content of oxygen defects in the catalytic material is 2-10%, preferably 4-6%. The advantage of adopting this preferred embodiment is that the catalytic material has a preferred electron concentration and a large number of surface active sites. When the oxygen defect content is not within this range, the number of active sites of the material is limited when the oxygen defect content is too small, and when the oxygen defect concentration is too high, it will affect the lattice stability, resulting in a decrease in material stability and affecting its reaction activity.

[0030] In the present invention, preferably, the catalytic material has photocatalytic activity in the range of 500-1000nm visible light and near-infrared light, that is, the catalytic material has a band-tail state absorption in the long wavelength range, indicating that the catalytic material has light absorption ability and catalytic reaction activity in the range of 500-1000nm visible light and near-infrared light. In the present invention, the band-tail state absorption has the meaning conventionally defined in the art, and the wider the visible light and near-infrared light range, the better the catalytic performance of the catalytic material. In the present invention, the band-tail state absorption is measured by an ultraviolet-visible spectrophotometer, and the specific test conditions are: the absorbance of the solid powder sample is tested using an integrating sphere.

[0031] A second aspect of the present invention provides a method for preparing a noble metal-supported catalytic material, wherein the method comprises the following steps: S1, contacting a dispersion A containing a Group VIII metal precursor and a first alcohol with a precipitant to obtain a solid reaction product; S2, in the presence of a reducing agent, subjecting the dispersion B containing the solid reaction product of step S1 and the second alcohol to a reduction reaction with a ruthenium precursor, and then drying to obtain a noble metal-supported amorphous metal oxide catalytic material; The Group VIII metal is selected from at least one of iron, cobalt and nickel; The amount of the ruthenium precursor is such that the content of ruthenium in the prepared noble metal-supported amorphous metal oxide catalyst material is 0.1-6.5% by mass, calculated as the element, based on the total amount of the catalyst material; The contact reaction conditions in step S1 include: temperature of 5-40° C. and time of 0.5-24 h.

[0032] The method provided by the present invention adopts a room temperature liquid phase synthesis method to prepare a catalytic material without high temperature conditions. The preparation method is simple and has good repeatability. The composition and structure of the catalyst are relatively easy to control. In addition, the energy consumption is low and it is conducive to industrial production. At the same time, the introduction of Group VIII metals and the precious metal ruthenium increases the active sites and improves the activity of the catalytic material.

[0033] In the present invention, preferably, the amount of the ruthenium precursor used is such that the content of ruthenium in the obtained noble metal-supported amorphous metal oxide catalyst material is 2-5% by mass, calculated as the element, based on the total amount of the catalyst material.

[0034] In the present invention, preferably, in step S1, the Group VIII metal is iron, cobalt and nickel. In the present invention, by selecting Group VIII metals and noble metal ruthenium for coordination, non-noble metals are introduced to increase active sites and improve reaction efficiency.

[0035] In the present invention, there is no particular limitation on the type of Group VIII metal precursor. Preferably, in step S1, the Group VIII metal precursor is selected from soluble compounds of various metals, more preferably at least one of nitrates, chlorides and sulfates, for example, cobalt nitrate, basic cobalt carbonate, ferric nitrate, ferric chloride, nickel nitrate, etc.

[0036] In the present invention, the mass ratio of the cobalt precursor to the sum of the nickel precursor and the iron precursor is controlled so that the components in the prepared catalytic material cooperate with each other to improve the catalytic performance of the catalytic material. Preferably, the mass ratio of the cobalt precursor calculated as oxide to the sum of the nickel precursor calculated as oxide and the iron precursor calculated as oxide is 1-5:1, and more preferably 1.2-3:1.

[0037] In the present invention, preferably, the dispersion A is prepared by dispersing a Group VIII metal precursor in a first alcohol. By dispersing the Group VIII metal precursor in the first alcohol, hydrolysis of the Group VIII metal precursor is avoided, thereby ensuring smooth subsequent reactions.

[0038] In the present invention, there is no particular limitation on the type of the first alcohol, as long as it can help disperse the Group VIII metal precursor and prevent the Group VIII metal precursor from hydrolyzing. Preferably, the first alcohol is a monohydric alcohol and / or a polyhydric alcohol, and is further preferably selected from at least one of methanol, ethanol and ethylene glycol. In the present invention, the polyhydric alcohol refers to an alcohol containing two or more hydroxyl groups, and the present invention does not make any particular limitation on its specific type.

[0039] In the present invention, there is no particular limitation on the amount of the Group VIII metal precursor and the first alcohol. Preferably, the mass ratio of the Group VIII metal precursor to the first alcohol is 1:1-10, preferably 1:1-5.

[0040] In the present invention, there is no particular limitation on the type of precipitant. Preferably, the precipitant is a carbonate and / or a bicarbonate, preferably at least one selected from potassium carbonate, sodium carbonate, ammonium carbonate, potassium bicarbonate, sodium bicarbonate and ammonium bicarbonate.

[0041] In the present invention, preferably, step S1 comprises: adding dispersion C containing a precipitant to dispersion A containing a Group VIII metal precursor and a first alcohol under stirring conditions to carry out a contact reaction. In the present invention, there is no limitation on the stirring method and specific conditions.

[0042] In the present invention, preferably, the dispersion C containing the precipitant is prepared by dispersing the precipitant in a solvent. In the present invention, there is no particular limitation on the type of solvent, as long as it helps to disperse the precipitant, such as water, and those skilled in the art can select it according to actual needs. In the present invention, there is no particular limitation on the amount of the precipitant and the solvent, and preferably, the mass ratio of the precipitant to water is 1:0.5-3.

[0043] In the present invention, the growth of the amorphous material is regulated by controlling the addition rate of the dispersion C to improve the catalytic performance. Preferably, the addition rate of the dispersion C containing the precipitant is 0.5-2.5 mL / min relative to 10 mL of the dispersion A containing the Group VIII metal precursor and the first alcohol. The advantage of adopting this preferred embodiment is that it is conducive to the uniform growth and mixing of the amorphous material.

[0044] In the present invention, the amount of the precipitant can be selected in a wide range. Preferably, in step S1, the mass ratio of the Group VIII metal precursor to the precipitant is 1:0.5-3.

[0045] In the present invention, preferably, in step S1, the contact reaction conditions include: temperature of 20-40° C. and time of 0.5-10 h. The advantages of adopting this preferred embodiment are to control the growth rate of amorphous oxide and improve the ammonia decomposition activity.

[0046] In the present invention, preferably, step S1 further comprises solid-liquid separation of the contact reaction product to obtain a solid reaction product of step S1. The present invention does not particularly limit the solid-liquid separation method, and those skilled in the art can select it according to actual needs.

[0047] In the present invention, preferably, in step S2, the dispersion B containing the solid reaction product of step S1 and the second alcohol is prepared by dispersing the solid reaction product of step S1 in the second alcohol.

[0048] In the present invention, the type of the second alcohol is not particularly limited, and the second alcohol may be the same as or different from the first alcohol, but is preferably the same as the first alcohol.

[0049] In the present invention, there is no particular limitation on the amount of the solid reaction product of step S1 and the second alcohol used in step S2. Preferably, in step S2, the mass ratio of the solid reaction product of step S1 to the second alcohol is 1:4-15.

[0050] In the present invention, there is no particular limitation on the type of ruthenium precursor. Preferably, in step S2, the ruthenium precursor is selected from soluble compounds of ruthenium, preferably at least one of ruthenium trichloride, ruthenium nitrate, ruthenium sulfate, ruthenium acetylacetonate, bis(pentamethylcyclopentene)ruthenium, bis(cyclopentene)ruthenium, and bis(cyclooctadiene)ruthenium chloride.

[0051] In the present invention, there is no particular limitation on the type of reducing agent, and strong reducing agents or weak reducing agents conventionally defined in the art are applicable to the present invention, preferably strong reducing agents. Preferably, in step S2, the reducing agent is sodium borohydride and / or potassium borohydride, more preferably sodium borohydride.

[0052] In the present invention, there is no particular limitation on the amount of the reducing agent. Preferably, in step S2, the mass ratio of the Ru precursor to the reducing agent in step S1 is 1:0.1-0.5. In the present invention, preferably, step S2 comprises: under stirring conditions, adding the ruthenium precursor to a dispersion B containing the solid reaction product of step S1 and the second alcohol, and then adding a reducing agent to carry out a reduction reaction. In the present invention, the specific manner and conditions of stirring are not particularly limited. It is understood that the reduction reaction in step S2 includes a reaction section and a reduction section, the reaction section refers to adding the ruthenium precursor to a dispersion B containing the solid reaction product of step S1 and the second alcohol to react, and the reduction section refers to reducing after adding a reducing agent. In the present invention, the conditions of the reduction reaction include the reaction conditions of the reaction section and the reduction section.

[0053] In the present invention, the range of selection for reduction conditions is relatively wide. Preferably, in step S2, the conditions for the reduction reaction include: temperature of 0-30°C, time of 1-8h; further preferably, in step S2, the conditions for the reduction reaction include: temperature of 10-15°C, time of 2-6h. It should be noted that the reduction temperature in the present invention refers to the reaction section temperature and the reduction section temperature. It should be further noted that the reaction section temperature and the reduction section temperature may be the same or different, preferably the same; the reduction time refers to the sum of the reaction section time and the reduction section time. The reaction section time and the reduction section time may be the same or different, preferably different. The reaction section time and the reduction section time are not particularly limited in the present invention.

[0054] In the present invention, preferably, step S2 also includes solid-liquid separation of the reduction reaction product to obtain a noble metal-loaded amorphous metal oxide catalytic material. The present invention does not specifically limit the solid-liquid separation method, and those skilled in the art can select it according to actual needs.

[0055] In the present invention, there is no particular limitation on the drying conditions in step S2. Preferably, in step S2, the drying conditions include: a temperature of 40-70°C and a drying time of 12-24 hours.

[0056] According to a specific embodiment of the present invention, the method for preparing a noble metal-loaded amorphous metal oxide catalytic material comprises the following steps: S1, dispersing a Group VIII metal precursor in a first alcohol to obtain a dispersion A, dispersing a precipitant in a solvent (preferably water) to obtain a dispersion C containing the precipitant, and then subjecting the dispersion A and the dispersion C containing the precipitant to a contact reaction and centrifugation to obtain a solid reaction product; S2, dispersing the solid reaction product obtained in step S1 in a second alcohol to obtain a dispersion B, adding a ruthenium precursor to the dispersion B and stirring, and then adding a reducing agent to carry out a reduction reaction to obtain a reduction reaction product, and finally washing, centrifuging and drying the reduction reaction product to obtain the noble metal-loaded amorphous metal oxide catalytic material.

[0057] The third aspect of the present invention provides a noble metal-loaded amorphous metal oxide catalytic material prepared by the preparation method described in the second aspect.

[0058] The fourth aspect of the present invention provides an application of the noble metal-loaded amorphous metal oxide catalytic material described in the first aspect or the third aspect in a photocatalytic ammonia decomposition hydrogen production reaction.

[0059] In the present invention, preferably, the photocatalytic ammonia decomposition reaction for producing hydrogen comprises: subjecting ammonia (preferably aqueous ammonia) to a photocatalytic ammonia decomposition reaction for producing hydrogen under visible light irradiation and in the presence of the catalytic material described in the first aspect or the third aspect.

[0060] In the present invention, preferably, the conditions of the photocatalytic ammonia decomposition to produce hydrogen reaction include: the reaction temperature is 0-70° C., and the amount of the catalyst is 0.05-1 g relative to 0.01 mol of ammonia.

[0061] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the raw materials used are from commercially available products.

[0062] Example 1 Weigh 23.3g of cobalt nitrate hexahydrate, 10.1g of ferric nitrate nonahydrate and 7.8g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C. The addition rate of dispersion C is 1.0mL / min relative to 10mL of dispersion A. After sufficient stirring for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B. Add 1.0g of ruthenium trichloride at a constant temperature of 10°C and stir the reaction for 3 hours. Quickly add 0.2g of sodium borohydride and stir the reaction for 2 hours. Wash the obtained solid with water, recover it by centrifugation and dry it at 60°C for 12 hours to obtain a precious metal-loaded amorphous oxide catalytic material. Figure 1As shown, the noble metal supported amorphous oxide catalytic materials have a o There is no diffraction characteristic peak corresponding to metal in the range of 30–40 o A broadened amorphous characteristic diffraction peak appears between the two, indicating that the catalytic material of Example 1 is an amorphous structure. Figure 2 It can be seen that the catalytic material responds well to near-infrared sunlight.

[0063] Example 2 Weigh 23.3g of cobalt nitrate hexahydrate, 7.6g of ferric nitrate nonahydrate and 9.7g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 60g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C, with a rate of addition of dispersion C of 1.5mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B, and add 0.54g of ruthenium trichloride at a constant temperature of 15°C and stir and react for 4 hours, quickly add 0.2g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0064] Example 3 Weigh 31.1g of cobalt nitrate hexahydrate, 5.0g of ferric nitrate nonahydrate and 3.9g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C, with a dispersion C addition rate of 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B, and add 1.0g of ruthenium trichloride at a constant temperature of 10°C and stir and react for 3 hours, quickly add 0.16g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0065] Example 4 Weigh 19.4g of cobalt nitrate hexahydrate, 12.6g of ferric nitrate nonahydrate and 9.7g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C, with a dispersion C addition rate of 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B, and add 1.0g of ruthenium trichloride at a constant temperature of 10°C and stir and react for 3 hours, quickly add 0.4g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0066] Example 5 Weigh 23.3g of cobalt nitrate hexahydrate, 10.1g of ferric nitrate nonahydrate and 7.8g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C, with a rate of 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B, and add 0.06g of ruthenium trichloride at a constant temperature of 10°C and stir and react for 3 hours, quickly add 0.03g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0067] Example 6 Weigh 23.3g of cobalt nitrate hexahydrate, 10.1g of ferric nitrate nonahydrate and 7.8g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 80g of sodium carbonate and disperse them in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C, with a dispersion C addition rate of 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 50mL of anhydrous ethanol to obtain dispersion B, and add 1.35g of ruthenium trichloride at a constant temperature of 15°C and stir and react for 3 hours, quickly add 0.4g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0068] Example 7 Weigh 23.3g of cobalt nitrate hexahydrate, 10.1g of ferric nitrate ninehydrate and 7.8g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C, with a dispersion C addition rate of 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B, and add 1.0g of ruthenium trichloride at a constant temperature of 0.5°C and stir and react for 3 hours, quickly add 0.2g of sodium borohydride and stir and react for 1 hour, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0069] Example 8 Weigh 38.9g of cobalt nitrate hexahydrate precursor and disperse it in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C. The addition rate of dispersion C is 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B. After adding 1.0g of ruthenium trichloride at a constant temperature of 10°C, stir and react for 3 hours, quickly add 0.2g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0070] Example 9 Weigh 50.5g of ferric nitrate nonahydrate precursor and disperse it in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C. The addition rate of dispersion C is 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B. After adding 1.0g of ruthenium trichloride at a constant temperature of 10°C, stir and react for 3 hours, quickly add 0.2g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0071] Comparative Example 1 Weigh 23.3g of cobalt nitrate hexahydrate, 10.1g of ferric nitrate nonahydrate and 7.8g of nickel nitrate hexahydrate and disperse them in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C. The addition rate of dispersion C is 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifugal recovery is obtained to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B, and add 1.0g of ruthenium trichloride at a constant temperature of 10°C and stir the reaction for 3 hours. Quickly add 0.2g of sodium borohydride and stir the reaction for 2 hours. Wash the obtained solid with water, centrifuge and recover it, and dry it at 60°C for 12 hours. Roast it at 500°C in a muffle furnace for 2h to obtain comparative example 1 (crystalline sample).

[0072] Comparative Example 2 Weigh 23.3g of cobalt nitrate hexahydrate, 10.1g of ferric nitrate nonahydrate and 7.8g of nickel nitrate hexahydrate and disperse them in 80mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 80°C, with a dispersion C addition rate of 1.2mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 8 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B, and add 1.0g of ruthenium trichloride at a constant temperature of 10°C and stir and react for 3 hours, quickly add 0.2g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0073] Comparative Example 3 Weigh 50.0g of manganese nitrate precursor and disperse it in 100mL of anhydrous ethanol to obtain dispersion A; weigh 50g of sodium carbonate and disperse it in 30mL of water to obtain dispersion C. Slowly add dispersion C to dispersion A at a constant temperature of 40°C. The addition rate of dispersion C is 1.0mL / min relative to 10mL of dispersion A. After fully stirring and reacting for 6 hours, centrifuge and recover to obtain a solid reaction product. Take 8g of the solid reaction product and disperse it in 60mL of anhydrous ethanol to obtain dispersion B. After adding 1.0g of ruthenium trichloride at a constant temperature of 10°C, stir and react for 3 hours, quickly add 0.2g of sodium borohydride and stir and react for 2 hours, wash the obtained solid with water, centrifuge and recover, and dry at 60°C for 12 hours to obtain a noble metal-supported amorphous oxide catalytic material.

[0074] The compositions of the catalytic materials in the above examples and comparative examples are shown in Table 1, and the property parameters are shown in Table 2.

[0075] Table 1 Catalytic material composition Example 1 60wt%CoO-20wt%Fe2O3-20wt%NiO / 4.6wt%Ru Example 2 60wt%CoO-15wt%Fe2O3-25wt%NiO / 2.6wt%Ru Example 3 80wt%CoO-10wt%Fe2O3-10wt%NiO / 4.6wt%Ru Example 4 50wt%CoO-25wt%Fe2O3-25wt%NiO / 4.7wt%Ru Example 5 60wt%CoO-20wt%Fe2O3-20wt%NiO / 0.3wt%Ru Example 6 60wt%CoO-20wt%Fe2O3-20wt%NiO / 6.2wt%Ru Example 7 60wt%CoO-20wt%Fe2O3-20wt%NiO / 4.6wt%Ru Example 8 100wt%CoO / 4.6wt%Ru Example 9 100wt%Fe2O3 / 4.6wt%Ru Comparative Example 1 60wt%CoO-20wt%Fe2O3-20wt%NiO / 4.6wt%Ru Comparative Example 2 60wt%CoO-20wt%Fe2O3-20wt%NiO / 4.6wt%Ru Comparative Example 3 100wt%M2O3 / 4.6wt%Ru Table 2 Photocatalytic ammonia decomposition to produce hydrogen activity test The noble metal-loaded amorphous oxide catalytic materials of the above-mentioned embodiment and comparative example were subjected to photocatalytic ammonia decomposition and hydrogen production reaction under simulated sunlight and long wavelengths greater than 600nm, and the activity test was carried out using an online vacuum photocatalytic reaction device, and the light source was a 300W xenon lamp. The reaction conditions are: 0.1g catalyst, 100mL, 0.1mol / L ammonia solution, and a reaction temperature of 5°C. After the reaction started, samples were taken every 1 hour, and the average reaction rate within 6 hours was calculated. The products were analyzed by chromatography equipped with a hydrogen flame ionization detector and a thermal conductivity cell detector, and quantified using a pre-determined standard curve. The reaction products are N 2 and H 2 and a small amount of O from the side reaction of water decomposition 2 The reaction results are shown in Table 3.

[0076] Table 3 It can be seen from Table 3 that the amorphous materials provided by the present invention have excellent photocatalytic ammonia decomposition performance, and also show good performance under long-wavelength light greater than 600nm, indicating that they can better utilize broad-spectrum solar energy. However, the crystallized sample of Comparative Example 1 obtained after high-temperature calcination is not a semiconductor material and does not have photocatalytic ability; compared with Example 1, the contact reaction temperature of Comparative Example 2 is too high, the amorphous structure of part of the catalytic material disappears, and the light response ability becomes poor; Comparative Example 3 shows that only the preferred metal oxide of the present invention has good photocatalytic ammonia decomposition performance.

[0077] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A noble metal-supported amorphous metal oxide catalytic material, characterized in that: The catalytic material includes amorphous metal oxide of Group VIII and ruthenium; the amorphous metal oxide of Group VIII is selected from at least one of amorphous nickel oxide, amorphous cobalt oxide and amorphous iron oxide; based on the total amount of the catalytic material, the content of ruthenium is 0.1-6.5% by mass in terms of element.

2. The catalytic material according to claim 1, wherein Based on the total amount of the catalytic material, the content of ruthenium is 2-5% by mass in terms of element; Preferably, the amorphous metal oxide of Group VIII is amorphous nickel oxide, amorphous cobalt oxide and amorphous iron oxide; Preferably, the mass ratio of the amorphous cobalt oxide to the sum of the amorphous nickel oxide and the amorphous iron oxide is 1-5:1, more preferably 1.2-3:1; Preferably, based on the total amount of the amorphous metal oxide of Group VIII, the content of the amorphous cobalt oxide is 50-80% by mass, the content of the amorphous nickel oxide is 7.5-25% by mass, and the content of the amorphous iron oxide is 7.5-25% by mass.

3. The catalytic material according to claim 1 or 2, wherein: The specific surface area of ​​the catalytic material is 200-800 cm 2 / g, preferably 600-800cm 2 / g; Preferably, the catalytic material has no characteristic diffraction peak at 10°-90° in the X-ray diffraction pattern, and the catalytic material has a characteristic diffraction peak of an amorphous package at 30°-40° in the X-ray diffraction pattern; Preferably, the catalytic material contains oxygen defects; Preferably, the content of oxygen defects in the catalytic material is 2-10%, more preferably 4-6%.

4. A method for preparing a noble metal-supported amorphous metal oxide catalytic material, wherein: The method comprises the following steps: S1, contacting a dispersion A containing a Group VIII metal precursor and a first alcohol with a precipitant to obtain a solid reaction product; S2, in the presence of a reducing agent, subjecting the dispersion B containing the solid reaction product of step S1 and the second alcohol to a reduction reaction with a ruthenium precursor, and then drying to obtain a noble metal-supported amorphous metal oxide catalytic material; The Group VIII metal is selected from at least one of iron, cobalt and nickel; The amount of the ruthenium precursor is such that the content of ruthenium in the prepared noble metal-supported amorphous metal oxide catalyst material is 0.1-6.5% by mass, calculated as the element, based on the total amount of the catalyst material. The contact reaction conditions in step S1 include: temperature of 5-40° C. and time of 0.5-24 h.

5. The method according to claim 4, wherein: The amount of the ruthenium precursor is such that the content of ruthenium in the prepared noble metal-supported amorphous metal oxide catalyst material is 2-5% by mass, calculated as the element, based on the total amount of the catalyst material; Preferably, in step S1, the Group VIII metal is iron, cobalt and nickel; Preferably, in step S1, the Group VIII metal precursor is selected from soluble compounds of various metals, and more preferably is at least one of nitrates, chlorides and sulfates; Preferably, the mass ratio of the cobalt precursor calculated as oxide to the sum of the nickel precursor calculated as oxide and the iron precursor calculated as oxide is 1-5:1, more preferably 1.2-3:1; Preferably, the first alcohol is a monohydric alcohol and / or a polyhydric alcohol, further preferably at least one selected from methanol, ethanol and ethylene glycol; Preferably, the mass ratio of the Group VIII metal precursor to the first alcohol is 1:1-10, preferably 1:1-5.

6. The method according to claim 4 or 5, wherein: In step S1, the precipitant is a carbonate and / or a bicarbonate, preferably at least one selected from potassium carbonate, sodium carbonate, ammonium carbonate, potassium bicarbonate, sodium bicarbonate and ammonium bicarbonate; Preferably, step S1 comprises: adding a dispersion C containing a precipitant to a dispersion A containing a Group VIII metal precursor and a first alcohol under stirring conditions to carry out a contact reaction; Preferably, the dispersion C containing the precipitant is prepared by dispersing the precipitant in a solvent; Preferably, the addition rate of the dispersion C containing the precipitant is 0.5-2.5 mL / min relative to 10 mL of the dispersion A containing the Group VIII metal precursor and the first alcohol; Preferably, in step S1, the mass ratio of the Group VIII metal precursor to the precipitant is 1:0.5-3; Preferably, in step S1, the contact reaction conditions include: temperature of 20-40° C., and time of 0.5-10 h.

7. The method according to claim 4 or 5, wherein: In step S2, the dispersion B containing the solid reaction product of step S1 and the second alcohol is prepared by dispersing the solid reaction product of step S1 in the second alcohol; Preferably, in step S2, the mass ratio of the solid reaction product in step S1 to the second alcohol is 1:4-15; Preferably, in step S2, the ruthenium precursor is selected from soluble compounds of ruthenium, and more preferably is at least one of ruthenium trichloride, ruthenium nitrate, ruthenium sulfate, ruthenium acetylacetonate, bis(pentamethylcyclopentene)ruthenium and bis(cyclooctadiene)ruthenium, (1,5-cyclooctadiene)ruthenium chloride.

8. The method according to claim 4 or 5, wherein: In step S2, the reducing agent is sodium borohydride and / or potassium borohydride; Preferably, in step S2, the mass ratio of the Ru precursor to the reducing agent in step S1 is 1:0.1-0.5; Preferably, step S2 comprises: adding the ruthenium precursor to a dispersion B containing the solid reaction product of step S1 and the second alcohol under stirring conditions, and then adding a reducing agent to carry out a reduction reaction; Preferably, in step S2, the reduction reaction conditions include: temperature of 0-30°C, time of 1-8h; Further preferably, in step S2, the reduction reaction conditions include: temperature of 10-15°C, time of 2-6h; Preferably, in step S2, the drying conditions include: temperature of 40-70°C and time of 12-24h.

9. The noble metal-supported amorphous metal oxide catalytic material obtained by the preparation method according to any one of claims 4 to 8.

10. Use of the noble metal-supported amorphous metal oxide catalytic material according to any one of claims 1 to 3 and 9 in a photocatalytic ammonia decomposition hydrogen production reaction.

Citation Information

Patent Citations

  • Amorphous composite material as well as preparation method and application thereof

    CN112359373A

  • Preparation method of supported ruthenium-based catalyst

    CN112387274A

  • Amorphous iron oxide nanosheet composite material as well as preparation method and application thereof

    CN114471612A

  • Amorphous FeOOH / polyacrylamide composite flocculant as well as preparation method and application thereof

    CN114873706A

  • Amorphous manganese oxide composite material as well as preparation method and application thereof

    CN115676896A